Chromosome-level genome assembly of Fragaria pentaphylla using PacBio and Hi-C technologies - Sun, Rui; Li, Shuangtao; Chang, Linlin; Dong, Jing; Zhong, Chuanfei; Zhang, Hongli; Wei, Lingzhi; Gao, Yongshun; Wang, Guixia; Zhang, Yuntao; Sun, Jian (Frontiers in Genetics, 2022)
Fragaria pentaphylla, a wild diploid quinquefoliolate species of Fragaria, is native to Southwest China. It has two morphs of red and white fruit color in nature and has characteristics of unique fragrance and resistance, which made it not only a valuable breeding material but also a potential model plant for molecular function researches. Here, we generate a high-quality chromosome-level genome assembly of a F. pentaphylla accession, BAAFS-FP039 employing a combination of PacBio Long-Read Sequencing, Illumina Short-Read Sequencing, and Hi-C Sequencing. The assembled genome contained 256.74 Mb and a contig N50 length of 32.38 Mb, accounting for 99.9% of the estimated genome (256.77 Mb). Based on Hi-C data, seven pseudo-chromosomes of F. pentaphylla-FP039 genome were assembled, covering 99.39% of the genome assembly. The genome was composed of 44.61% repetitive sequences and 29,623 protein-coding genes, 97.62% of protein-coding genes could be functionally annotated. Phylogenetic and chromosome syntenic analysis revealed that F. pentaphylla-FP039 was closely related to F. nubicola. This high-quality genome could provides fundamental molecular resources for evolutionary studies, breeding efforts, and exploring the unique biological characteristics of F. pentaphylla.